The Rising Incidence of Atypical Post-Streptococcal Glomerulonephritis in Children: A Meta-Analysis and Implications for Diagnosis and Management - Ni Luh Ayudimartini (HM Publisher, 2025)
Post-streptococcal glomerulonephritis (PSGN) is a common cause of acute nephritis in children. While typically presenting with classical features, atypical presentations are increasingly recognized, posing diagnostic and management challenges. This meta-analysis aimed to evaluate the rising incidence of atypical PSGN in children and explore its implications for clinical practice. A systematic search of PubMed, Embase, and Cochrane Library was conducted for studies published between 2013 and 2024 reporting on atypical PSGN in children. Data extracted included incidence rates, clinical presentations, laboratory findings, treatment strategies, and outcomes. A random-effects model was used to pool data and assess heterogeneity. Six studies (n=1248 children with PSGN) were included. The pooled prevalence of atypical PSGN was 28.7% (95% CI: 25.9-31.6%; I2= 68%). Clinical Presentations of Atypical PSGN included Nephrotic syndrome: 14.4% (95% CI: 12.2-16.8%), Isolated hematuria: 10.5% (95% CI: 8.8-12.4%), Rapidly progressive glomerulonephritis (RPGN): 4.2% (95% CI: 3.2-5.5%), Acute kidney injury (AKI): 8.7% (95% CI: 7.1-10.4%). Atypical PSGN was associated with a higher risk of complications (odds ratio [OR] 1.8, 95% CI: 1.3-2.5) and a longer duration of hospitalization (mean difference 2.7 days, 95% CI: 2-3.4). In conclusion, atypical PSGN is increasingly common in children, presenting with diverse clinical manifestations. Clinicians should maintain a high index of suspicion for atypical presentations to ensure prompt diagnosis and appropriate management. Further research is needed to identify risk factors for atypical PSGN and optimize treatment strategies.